التنمية المحلية في الجزائر: دراسة في الفواعل والمحددات - إنزارن, عادل (جامعة الوادي University of Eloued, 2017)
تعتبر سياسة التنمية المحلية ركيزة أساسية لبناء نموذج تنموي متكامل في الدولة، وحاولت هذه الدراسة إبراز أهم الفواعل المحلية الرسمية وغير الرسمية في رسم السياسة العامة التنموية على المستوى المحلي في الجزائر، ومعالجة أهم المحددات التي تؤثر فيها سواء على مستوى البيئة الداخلية أو البيئة الخارجية. وذلك بهدف بناء مقاربة للتنمية المحلية تقوم على إشراك جميع الفواعل في التنمية المحلية، وتوفير بيئة مناسبة على جميع المستويات لتجسيد تنمية محلية مستدامة. Abstract: Local development policy is cosidered as a fundamental pillar of constructing an integrated developmental model in the state. This study try to highlight the most important official local actors and non-local actors to draw the general policy at the local level in Algeria. In addition to, address the most important determinants that affect them on both the internal and external environment levels. The aim of constructing an approach to local development based on the involvement of all actors in local development, and provide a suitable environment at all levels to reflect the durable local development.
Keywords: التنمية المحلية؛ اقتصاد السوق؛ دعم النمو؛ المجتمع المدني